A vision-based system for monitoring block assembly in shipbuilding. (February 2015) - Kim, Minsung; Choi, Woosung; Kim, Byung-Chul; Kim, Hokyeong; Seol, Jae Hun; Woo, Jonghun; Ko, Kwang Hee
Abstract: A ship is constructed using blocks, which are the basic units in shipbuilding. Each block is designed and assembled individually and welded together to form an entire ship. Therefore, the assembly of blocks within a manufacturing schedule is important for the timely delivery of a ship. To maintain the block assembly schedule, the current status of the block assembly must be monitored, and fed back to the schedule operator. Currently, monitoring of the assembly status is performed manually by the worker, who determines the status of assembly of the block based on his/her experiences. Therefore, the efficiency and accuracy of the work cannot be guaranteed in the current practice. To address this problem, a vision-based system for monitoring block assembly is proposed in this work. The system consists of segmentation, identification and estimation units. Cameras acquire images of the blocks during assembly. The images are subsequently processed to extract the areas of the blocks. Next, the extracted blocks are identified and compared with CAD data for estimating the assembly progress. The estimated information is provided to the operator for efficient management of the block assembly schedule. The proposed system was tested with real examples that demonstrate the potential for use in a real assembly site.